Baseline Features Influencing the Effectiveness of Retraining Therapy for Writer's Cramp. Issue 3 (30th March 2015) - Bleton, Jean‐Pierre; Touzé, Emmanuel; Soulez‐la‐Rivière, Laure; Baizabal‐Carvallo, José Fidel; Guignier, Françoise; Cambriel, Claire; Sangla, Sophie; Grabli, David; Roze, Emmanuel; Mesure, Serge; Vidailhet, Marie
Abstract: Background: The effectiveness of retraining therapy (RT) for writer's cramp is difficult to predict and its determinants are unknown. Methods: We examined factors potentially predicting improved legibility after RT in patients with writer's cramp (WC). We reviewed the files of 693 WC patients treated with RT from 1995 to 2009. Standardized assessments were made both at baseline and after 2 months of RT in 305 patients. The effect of RT on legibility was evaluated by using the handwriting subscore of the Burke‐Fahn‐Marsden (BFM) disability scale. Initial and final handwriting samples were blindly scored in random order. Associations between WC patterns and changes in legibility were identified by uni‐ and multivariable analyses. Results: Legibility improved by ≥1 point in the BFM handwriting subscore in 93 patients (31%). WC patients who improved were more likely to have synergic dystonic patterns involving the wrist and forearm (60% vs. 40%; P = 0.03) and less likely to have flexion of fingers F3 to F5 (19% vs. 81%; P = 0.017). Outcome was not related to gender, age, or dystonia duration. Our results confirm that retraining therapy could improve legibility in patients with writer's cramp. Conclusions: The pattern of writer's cramp can help to identify patients who are most likely to benefit from retraining therapy, regardless of age, gender, and disease duration.